2007
DOI: 10.1074/jbc.m611392200
|View full text |Cite
|
Sign up to set email alerts
|

RNA Binding-independent Dimerization of Adenosine Deaminases Acting on RNA and Dominant Negative Effects of Nonfunctional Subunits on Dimer Functions

Abstract: RNA editing that converts adenosine to inosine in doublestranded RNA (dsRNA) is mediated by adenosine deaminases acting on RNA (ADAR). ADAR1 and ADAR2 form respective homodimers, and this association is essential for their enzymatic activities. In this investigation, we set out experiments aiming to determine whether formation of the homodimer complex is mediated by an amino acid interface made through protein-protein interactions of two monomers or via binding of the two subunits to a dsRNA substrate. Point m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
114
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 47 publications
(113 reference statements)
10
114
0
Order By: Relevance
“…Previous studies of ADAR3 demonstrated that mutation of these lysine residues to glutamate (E) and alanine (A) disrupts dsRNA binding in vitro (60). Western blotting of U87 cells transduced with retroviruses expressing the ADAR3 mutants driven by the CMV promoter resulted in similar expression levels as the U87 cells stably expressing wildtype ADAR3 driven by the CMV promoter (Fig.…”
Section: Adar3 a Regulator Of Glutamate Receptor Editingmentioning
confidence: 71%
“…Previous studies of ADAR3 demonstrated that mutation of these lysine residues to glutamate (E) and alanine (A) disrupts dsRNA binding in vitro (60). Western blotting of U87 cells transduced with retroviruses expressing the ADAR3 mutants driven by the CMV promoter resulted in similar expression levels as the U87 cells stably expressing wildtype ADAR3 driven by the CMV promoter (Fig.…”
Section: Adar3 a Regulator Of Glutamate Receptor Editingmentioning
confidence: 71%
“…Consistent with its nuclear localization, ADAR1 interacted with endogenous DGCR8 (Figure 5B), but its interaction with DICER was barely detectable under our experimental conditions. In addition, both the catalytically inactive ADAR1 mutant (E912A) [22,50] and the RNA-bindingnull ADAR1 mutant (EAA) [51] acted in a similar manner in the association with DGCR8 ( Figure 5B and data not shown), indicating that these ADAR1 mutations do not affect its association with DGCR8.…”
Section: Adar1 Acts As An Rna-binding Protein That Directly Inhibits mentioning
confidence: 73%
“…O-phenanthroline, a chelator of zinc ions, inhibits the enzymatic activity of purified natural ADAR1 (Kim and others 1994a). The catalytically active form of ADAR1 is a dimer (Cho and others 2003;Gallo and others 2003;Valente and Nishikura 2007). Fluorescence resonance energy transfer (FRET) and immunoprecipitation analyses have further demonstrated that both ADAR1 and ADAR2 form homodimers in human cells, that ADAR1 and ADAR2 may also form heterodimers, and that the dimerization likely is RNA-independent (Chilibeck and others 2006;Cenci and others 2008).…”
Section: Adar1 Proteinsmentioning
confidence: 99%